The Influence of Thermal Treatment on the Structure and Morphology of Iron Borosilicate Glasses - Fawzeya Gharghar; Sammer El-Jadal (African Journal of Advanced Pure and Applied Sciences, 2025)
The effect of heat treatment on the structure and morphology of iron borosilicate glass was analyzed using x-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and high-resolution transmission electron microscopy (TEM) coupled with electron diffraction pattern (EDP) technique. The selected samples were being subjecting to heat treatment at 650OC for 4 hr. FTIR measurements of the heat-treated samples revealed a significant decrease in the peak intensity associated with threefold-coordinated B–O bonds, accompanied by a significant increase in the band intensity corresponding to the tetrahedral units. According to XRD observation, the disappearing of diffraction peaks for the selected samples after heat treatment confirms the vitreous nature of the observed samples. TEM-EDP patterns revealed a reduction in the cluster size with the addition of Fe2O3 content, indicating the high ability of iron to withdraw non-bridging oxygens (NBOs) from silicate network and to behave as a glass former. On the other hand, the increasing in the particles number and aggregations that distributed in the internal structure is primarily attributed to the high temperature reached during thermal treatment.